Healthcare System Resilience in Crisis: The Role of District General Hospital Matale in Disaster Preparedness and Response – Experiences from Cyclone Ditwah - Fernando G. H. S.; Saddasena G. M. I. O.; Wijethunga R. S.; Basnayake K.; Rauf R.; Rathninda P. (International Journal of Innovative Science and Research Technology, 2026)
Introduction: Cyclone Ditwah in November 2025 exposed the vulnerabilities and resilience of Sri Lanka’s healthcare system, severely disrupting essential services and displacing large populations. District General Hospital Matale emerged as a pivotal institution, simultaneously delivering urgent medical care, coordinating disaster response, and sustaining staff welfare under extreme conditions. This case study underscores the hospital’s dual role as a healthcare provider and community anchor, offering critical insights into strengthening resilience and governance in resource-constrained settings.  Objectives: To strengthen healthcare resilience by analyzing the preparedness, response, and strategic interventions of District General Hospital Matale during Cyclone Ditwah, with the aim of informing future disaster management frameworks in Sri Lanka.  Method: The study employed a qualitative case study approach, analyzing District General Hospital Matale’s disaster preparedness, activation of protocols, and strategic interventions during Cyclone Ditwah. Data were drawn from hospital records, staff experiences, and district disaster management reports to evaluate resilience and lessons learned.  Result: DGH Matale managed disaster care despite flooding, power and water failures, and staff shortages. The hospital recorded 9 deaths and 19 injuries locally, while nationwide losses reached 410 deaths and 336 missing. Through 18 mobile medical camps, care was delivered to 711 displaced individuals, and the Sahana Sewa Program provided food, clothing, and essentials—sustaining operations and reinforcing community trust.  Discussion: DGH Matale’s experience shows that healthcare resilience depends on proactive preparedness, structured response, and community outreach, enabling hospitals to act as both clinical and humanitarian anchors during crises.  Conclusion: Cyclone Ditwah revealed both vulnerabilities and resilience in Sri Lanka’s healthcare system, with DGH Matale sustaining care through proactive leadership and teamwork. Its multidimensional response—spanning infrastructure, staff welfare, and community outreach—underscores hospitals as vital anchors of stability in crises.